Intellectual capital and development from a sociological perspective (analytical study) - عمعوم عبد الله حسين حمد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The problem of the study is that the absence or weakness of intellectual capital represents an obstacle to the development of less developed regions, especially in developing countries or those witnessing internal disagreements or conflicts. Iraqi educational institutions are also concerned with the production of intellectual capital. On the other hand, they adopted policies that resulted in the laws of privatization of education to reduce On the shoulders of the state, it has contributed to creating a reality that is not devoid of negatives, the spread of corruption, a lack of quality, and faltering development, and thus educational outcomes cannot compete in the local and global market. The study aimed to identify the importance of intellectual and cognitive capital in development processes, shed light on the most important sources of intellectual capital, identify the obstacles and challenges facing intellectual capital, and reach proposals for adopting an educational policy that achieves intellectual capital that contributes to development and meets the aspirations of Iraqi society. Regarding the importance of the study, intellectual capital comes from being the most valuable asset in light of the knowledge economy and constitutes the competitive advantage for current organizations and institutions that adopt creative intellectual products and keeping pace with the wide interest in the subject of intellectual capital at the level of international organizations to adopt research programs on intellectual capital as it is effective wealth in Achieving development, excellence, and creating creativity and innovation. From previous studies related to the subject of the study (Iraqi, Arab, and foreign) , the theories explaining the study are the theory of organizations, which assumes that institutions are a social unit created by society to satisfy certain needs, and this unit exercises its work within the framework of a specific social environment or with other units or organizations in society and works in The framework of the general goal of society, and that the nature of the goals that organizations or institutions seek to achieve depends on the positive role they provide through their programs and projects that they present to achieve their goals in a sustainable manner, with the intellectual capital they possess that contributes to achieving economic and social development, and through this theory the researcher can Identify the obstacles that organizations or institutions face through social construction, the nature of relationships and interactions, and the quality of the inputs and outputs of the organization and educational institution that work within the framework of the general goal of society. The type of study is descriptive and analytical, based on the theoretical framework of intellectual capital in organizations and institutions built by society. The study reached some results: the success of development and achieving its goals contributes to the development of society, and increasing intellectual capital is linked to the quality of university education, and incomplete development in its political and economic aspects. Social, health and educational capital does not create knowledge capital, due to the absence of attracting qualified individuals and selecting them for jobs in community institutions, including education.